REDISCOVERY OF CAMELLIA TONKINENSIS (PIT.) COHEN-STUART (THEACEAE) ON MT. BA VI, HANOI, VIETNAM - Anh Vinh Le; Hieu Nguyen; Thanh Son Hoang; Anthony S. Curry (Tạp chí Khoa học Đại học Đà Lạt)
Camellia specimens were collected from Mt. Ba Vi, Ba Vi National Park, during field surveys in 2022 (flowers) and 2023 (fruit). On the basis of morphological analyses, we determined that the morphology of these specimens matched that of Camellia tonkinensis. The characteristics of the specimens included papery-textured, elliptic or broad elliptic leaves with acuminate to narrowly acuminate apices, obtuse to rounded bases, petioles with channeled adaxial surfaces, tomentose gynoecia, 3(–4)-coccate capsules, and 1(–2) seeds per locule. A comparison of the morphological characteristics of the 2022 and 2023 collections (DL 220901, Dl 230201) was made with the type specimen (B. Balansa 3860, 1887) and the 2014 collections from Ngoc Son-Ngo Luong Nature Reserve (N. Q. Hieu et al. CPC616, CPC673, CPC712, CPC776). The characteristics and photographs of the rediscovered species from Mt. Ba Vi are presented herein. From the latest field surveys, the IUCN conservation status of Camellia tonkinensis was assessed as Critically Endangered (CR).